Exploring Batik Semarangan as a medium to develop intercultural communication awareness and global competence - Ekawati Marhaenny Dukut (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2023)
People doing work from home are mostly depending on what the internet has to offer for communication. Because people want to make good use of the Internet for communication, such information is available in English as a global language. One of the advantages of having ready information in English is that local cultural products can now have better chances to compete globally with products from other cultures. One of those products is Indonesia’s Batik Semarangan, which is produced in Semarang, the capital city of Central Java. Through studying the motifs found in Batik Semarangan, an intercultural communication awareness of rich hybrid culture can be achieved. To ensure awareness, a group of English Department’s literature students was trained to do library and field research on Batik Semarangan. By applying Roland Barthes’ semiotics, students were encouraged to explore the hidden reasons for the unique choice of Batik Semarangan motifs. By doing this activity, not only were the students equipped to be more critical in researching local products but the lecturer has also helped preserve and elevate Batik as a traditional heritage that has global potentiality. Keywords: Batik Semarang; cultural hybrid; traditional heritage; global competence; intercultural communication awarenessMenggali Batik Semarangan sebagai media untuk membentuk pengetahuan komunikasi antar budaya dan kompetensi globalKebanyakan orang yang melakukan pekerjaan mereka dari rumah mengandalkan media komunikasi mereka dengan apa yang ditawarkan oleh internet. Karena orang ingin memanfaatkan internet dengan baik untuk komunikasi, maka banyak informasi tersedia dalam bahasa Inggris sebagai bahasa global. Salah satu keuntungan memiliki informasi dalam bahasa Inggris adalah produk budaya lokal sekarang dapat memiliki peluang yang lebih baik untuk bersaing secara global dengan produk dari budaya lain. Salah satunya adalah Batik Semarangan Indonesia yang diproduksi di Semarang, ibu kota Jawa Tengah. Melalui mempelajari motif yang ditemukan di Batik Semarangan, kesadaran komunikasi antarbudaya akan budaya hibrida yang kaya dapat dicapai. Untuk memastikan kesadaran tersebut, sekelompok mahasiswa Sastra Inggris dilatih untuk melakukan penelitian kepustakaan dan lapangan tentang Batik Semarangan. Dengan menerapkan semiotika Roland Barthes, mahasiswa didorong untuk mengeksplorasi alasan-alasan tersembunyi dari pemilihan motif batik Semarangan yang unik. Dengan melakukan kegiatan ini, siswa tidak hanya dibekali untuk lebih kritis dalam meneliti produk lokal tetapi dosen juga turut melestarikan dan mengangkat Batik sebagai warisan tradisional yang memiliki potensi global.Kata kunci: Batik Semarangan; hibrida budaya; warisan tradisional; kompetensi global kesadaran komunikasi antarbudaya